Assessment of Impact of the ARIADNE Research: Insights Into Improving Access in Mental Health - Rahul Bhattacharya; Emanuele Valenti; Domenico Giacco (BJPsych Open, 2025)
Aims: Enduring inequalities in mental healthcare exist between UK minority ethnic and White British groups, which were further aggravated during the pandemic. Through 2022–23 the nationally funded ARIADNE research project carried out qualitative research and co-production workshops to suggest local (in four participating sites of England) and also identified over-arching solutions to improve access and experience of care. After the ARIADNE research project ended, a further co-designed impact analysis initiative was carried out in 2024 in two original participating sites (Coventry/Warwickshire and East London).